The Realm of Brave Men? Narratives on the Development of the Transylvanian Carpathians Around 1900 - Cotârlea, Delia (Universitatea Transilvania Brasov, 2024)
This article aims to trace narratives about the beginnings of mountaineering in Transylvania to determine the extent to which well-known members of Transylvanian mountaineering associations are subject to processes of heroization through socio-cultural practices. Therefore, we will first deal with strategies and techniques of heroization in order to then outline the historical development of the Siebenbürgischer Alpenverein (Transylvanian Alpine Association) (1873) and the Siebenbürgischer Karpathenverein (Transylvanian Carpathian Association) (1880) and to interpret their practices in the context of possible heroization processes.
Keywords: Carpathian Exploration; Transylvanian Carpathian Association; Heroization Processes